Nivel de conocimiento sobre el cáncer cervical y el Papanicolaou en relación al temor, estrés o vergüenza al tamizaje: Estudio transversal en una comunidad pobre - Castro, Miriam (2005)
OBJECTIVE: To examine the association between the levels of Papanicolaou (Pap) test and cervical cancer knowledge with fear, stress, or shame related to these. DESIGN: A simple random sample of all households within the community was conducted. MATERIAL AND METHODS: A survery was administered to women in a low socioeconomic community of Lima, Peru. Chisquare analysis, odds ratios and 95% confidence intervals were used to measure association of the variables studied with fear, stress, or shame. Logistic regression was used to control for confounding variables. RESULTS: From 300 women interviewed ages between 18 and 50, 20% had their last Pap test over two years and another 20% had never had a Pap smear. Nineteen percent (57) of women reported a high level of lear, stress or shame to the Pap test and cervical cancer, all associated to adolescence (OR 5,5 CI95% 1,8 16,9), living in Lima 5 years or less (OR 2,6 CI95%1,3-5,2), no sexual partner during the last year (OR 2,1 CI95% 1,1-7,6), no pregnancies (OR 3,1, CI95% 1,2-8,0), never having a Pap test (OR 4,7, CI95% 1,9-8,7), low or fair knowledge on Pap smear or cervical cancer (OR 4,1, CI95% 2,2-7,9). With multivariate analysis the correlation of being adolescent and low or fair knowledge on Pap and cervical cancer persisted. CONCLUSION: We suggest a community-based intervention informing the community about Pap smear and cervical cancer in order to improve negative perception of the Pap screening.